Abu Ja'far Mansur Was The Greatest Politician of The Abbasids - Ujang Tholib (Buletin Al-Turas, 2008)
During the reign of Abu Ja far a-Mansur, the second Abbasid caliph, several revolts broke outundermining the newly established caliphate. The revolts were launched by the two brothers of the HasanidAlids: Muhammad al-Nafs al-Zakiyya and Ibrahim b. Abdullah. Another revolt came from al-Mansur's uncle, Abdullah b. Ali who claimed the right of succession to the caliphate. With his cunning and slyness al-Mansur was able to crush these uprisings. He also succeeded in eliminating his great rival, Abu Muslimwho had rendered a great service to the Ab- basids. Due to an intense enmity between al-Mansur and Abu Muslim and the latter's rebellion, the caliph murdered him ruthlessly.